Sequential Diels–Alder/[3,3]-sigmatropic rearrangement reactions of β-nitrostyrene with 3-methyl-1,3-pentadiene - Wade, Peter A.; Pipic, Alma; Zeller, Matthias; Tsetsakos, Panagiota (Beilstein Journal of Organic Chemistry, 2013)
The tin(IV)-catalyzed reaction of β-nitrostyrene with (E)-3-methyl-1,3-pentadiene in toluene afforded two major nitronic ester cycloadducts in 27% and 29% yield that arise from the reaction at the less substituted diene double bond. Also present were four cycloadducts from the reaction at the higher substituted diene double bond, two of which were the formal cycloadducts of (Z)-3-methyl-1,3-pentadiene. A Friedel–Crafts alkylation product from the reaction of the diene, β-nitrostyrene, and toluene was also obtained in 10% yield. The tin(IV)-catalyzed reaction of β-nitrostyrene with (Z)-3-methyl-1,3-pentadiene in dichloromethane afforded four nitronic ester cycloadducts all derived from the reaction at the higher substituted double bond. One cycloadduct was isolated in 45% yield and two others are formal adducts of the E-isomer of the diene. The product formation in these reactions is consistent with a stepwise mechanism involving a zwitterionic intermediate. The initially isolated nitronic ester cycloadducts underwent tin(IV)-catalyzed interconversion, presumably via zwitterion intermediates. Cycloadducts derived from the reaction at the less substituted double bond of (E)-3-methyl-1,3-pentadiene underwent a [3,3]-sigmatropic rearrangement on heating to afford 4-nitrocyclohexenes. Cycloadducts derived from the reaction at the higher substituted diene double bond of either diene failed to undergo a thermal rearrangement. Rates and success of the rearrangement are consistent with a concerted mechanism possessing a dipolar transition state. An initial assessment of substituent effects on the rearrangement process is presented.
Keywords: cycloaddition; diene; nitro; nitronate; rearrangement